Prevention of Injuries in the Young Dancer - Solomon, Ruth; Solomon, John; Micheli, Lyle J. (Contemporary Pediatric and Adolescent Sports Medicine,, 2017)
Focusing exclusively on injury treatment and prevention in the young dancer, this comprehensive text addresses the unique needs of these athletes and stresses how their bodies differ in significant ways from adults', requiring that their training and clinical management be overseen by specialized personnel. The book opens with a discussion of the epidemiology of injury in the young dancer, followed by a description of screening procedures and a sample screening program. Physical therapy and resistance training are then covered, along with common conditions and injuries at the spine, hip, knee, and foot and ankle complex. Additional chapters discuss the use of diagnostic and interventional ultrasound, nutrition and bone health, psychological issues such as anxiety, eating disorders and peer relationships, and lastly the prevention of degenerative hip injuries. Prevention of Injuries in the Young Dancer is an essential resource with regard to the physical and psychological challenges facing young performers. It is relevant reading for dance medicine, sports medicine, and orthopedic professionals, as well as dancers, their parents, and especially those persons who promote their careers.